Nest structure and notes on the social behavior of Augochlora amphitrite (Schrottky) (Hymenoptera, Halictidae) - Dalmazzo, Maria de Los Milagros (2012)
The nesting biology of Augochlora (Augochlora) amphitrite (Schrottky) in a natural reserve in the Province of Buenos Aires, Argentina, is described. The species nests in decaying wood. Two types of nest architecture were found, which differed according to the substrate where they were built, either soft or hard wood. Nests in soft wood had the cells grouped in clusters surrounded by a cavity, and the clusters were supported by a varying number of pillars. Nests constructed in decomposing portions of cracks in otherwise hard wood had the cells constructed against the walls, without any pillars or surrounding cavity. Cells of both types of nests were oriented in all directions, without any detectable pattern. Measurements and characteristics of the nests are tabulated and compared to those known for other species of Augochlora s. str. Behavioral observations of active nests are indicative of a social division of tasks in Augochlora amphitrite. Such observations include nests with several females, some of which were never observed outside the nests, females with different degrees of wear and of ovary development, and at least one female that actively collected pollen which had much worn mandibles and wings, and undeveloped ovaries, all characteristics of the worker caste in social halictids.